المصطلحات الشرعية و نطقها في الموسوعة الفقهية الكويتية بين اللغة العربية و الإندونيسية دراسة تقابلية في علم الأصوات - SAFRUDDIN BADERAN; MUSTAFA ABDUL JABBAR (Rayah Al-Islam, 2016)
Among the realities that exist in learning Arabic in Indonesia is that Indonesian students face various difficulties in the learning process, this is due to differences in character and characteristics between Arabic and Indonesian one of which is the pronounciation of phonemes between the two languages. Therefore this study aims to reveal the term syari in the jurisprudence encyclopedia Kuwait between Arabic and Indonesian and to know the change in meaning and pronounciation after the transition into Indonesian, then analyze the way the phoneme is pronounced and how it is used to corret the pronounciation method for Indonesian students. As for the research method the author uses a descriptive and analytical approach. The author uses an analytical method that is by comparing the way the phoneme is pronounced from the term syari term between Arabic and Indonesian.Then the author divides it into four parts, the first Arabic phoneme which has no similarities to the Indonesian phoneme, the second Arabic phoneme which has similarities to the Indonesian phoneme, the third Arabic phoneme which has an equation with the Indonesian phoneme and the fourth phoneme Indonesian which has no similarities with Arabic phoneme. This research proves the existence of the term syari (absorption from Arabic) in the jurisprudence encyclopedia of Kuwait and proves that there is a change in meaning and pronounciation after switching to Indonesian, besides this research also proves a positive impact in correcting the pronounciation of phonemes in the learning process for Indonesian students.